Effect of pruning and nitrogen on leaf-nutrient status of peach (Prunus persica) - Singh, Devi; Chauhan, J S; Kaith, N S (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1990 and 1991 to study the effect of pruning intensity and N level on leaf-nutrient status of an 8-year-old 'July Elberta' peach [Prunuspersica (L.) Batsch] tree. The treatments were light, medium and heavy pruning and retention of 700-750 nodes/tree. and application of N @ 300, 400, 500, 600 and 700 g/tree. An increase in pruning severity increased the content of N, K, Fe and Mn (2.89-3.05%, 2.30-2.53%, 141.1-152.2 ppm and 166.3--182.3 ppm respectively) in the leaves, but decreased that of Ca and Cu (2.82-2.59% and 18.87-17.33,ppm respectively); and did not affect that of P, Mg and Zn. An increase in N level increased the content of N, Fe, Mn and Zn (2.87-3.07%. 135.6-161.7 ppm, 150.0-199.4 ppm and 7.59-10.00 ppm respectively) in the leaves and decreased that of P, K, Ca and Cu (0.218-0.205%. 2.56-2.25%, 2.89-2.49% and 19.22-16.59 ppm respectively). However, N level did not affect the Mg content in leaf significantly. The interaction between pruning intensity and N level was non-significant.